Castles : King Arthur's treasure - Appleby, Howard (London : Macmillan education, 2019)
This is a six-level series of readers for children learning english.
The Macmillan Children$1 (Bs Readers Level 5 will capture a child$1 (Bs interest in reading and learning English with fun and informative subject matter. The wide range of fiction and non-fiction titles provides reinforcement of basic structures and vocabulary and can be used alongside any primary course.s
Includes activities and a picture dictionary or wordlist.
Keywords: Juvenile literature; Readers (Primary); English language -- Study and teaching (Primary); Children's books